Project Citizen Model in Citizenship Education and Its Impact on Critical Thinking Skills for Elementary School Teacher Education Students - Handayani, Mella Indra; Haryanto, Haryanto; Wibowo, Ari (International Journal of Elementary Education, 2022)
Civic education is one of the subjects that play an important role in creating and realizing smart and good citizenship. Students are expected to have intellectual skills in the life of the nation and state, then their knowledge and skills will form a character in students which is used as a habit of daily life and reflects good citizens. One of the instructional treatments in Civics learning to achieve the above objectives is Project citizen. This study aims to analyze the effect of student critical thinking by applying the project citizen learning model to second-semester students of the Elementary School Teacher Education S1 study program. This research is quantitative research with a quasi-experimental method. The research was carried out with 50 students as research subjects. The data collection technique used a test. The results showed that applying the project citizen learning model with the stages of identifying problems, choosing problems as class study material, gathering information, developing class portfolios, presenting portfolios, and reflecting on learning experiences, can improve students' critical thinking. The test of the experimental class evidences this taught using the Project citizen learning model, which has a higher average value than the control class taught using the conventional model.